Web-Based Multi-Cafe Information System in the West Jakarta Area - Luthfia Fauzia Dewi Ariyanti; Janu Ilham Saputro; Eduard Hotman Purba; Muhammad Nur Habibie (Journal Collabits, 2026)
Evolving urban lifestyles have driven increased public interest—particularly in West Jakarta—in visiting cafes for relaxation, work, and socializing. However, information regarding cafe locations, menus, prices, facilities, and operating hours remains fragmented and difficult to access centrally, making it challenging for potential customers to make informed choices. This research aims to design and develop a web-based information system that integrates data from various cafes in West Jakarta into a single, unified platform. The system development follows the Waterfall model, encompassing requirements analysis, system design, implementation, testing, and maintenance. The system was built using web-based programming languages and a relational database to store cafe information, incorporating features such as search functionality, location- and category-based filtering, and user reviews. System testing utilized the Black Box Testing method to ensure all functions operated according to requirements, alongside usability testing to assess the system's ease of use for end-users. The results indicate that this multi-cafe information system enables users to quickly and accurately search for and compare cafe information while simultaneously assisting cafe owners in digitally promoting their businesses. This system is expected to serve as a beneficial, unified information solution for both the public and cafe business owners in West Jakarta.